Respuestas

2012-07-08T02:07:14+02:00

3x^2 -5x -2 =0

 

(3x +1)(x-2) = 0 

 

… alguno de los terminos es = 0 

 

3x +1 =0 ,  x = -1/3 

 

x-2 = 0   ,  x = 2 

 

b) 6x^2 - 6 = 5x

 

6x^2 -5x - 6  = 0 

 

(3x +2 )(2x -3) = 0 

 

… alguno de los terminos es = 0 

 

3x +2 = 0 ,  x = -2/3 

 

2x-3 = 0  ,   x = 3/2 

 

 

c) 2x+5 = 16x^2 

 

16x^2 -2x -5 = 0 

 

(2x +1)(8x -5) = 0 

 

 …

 

x= -1/2  ;  x = -5/8

 

d) x^2 -6 -5x = 0 

 

(x+1)(x-6)

 

x= -1  ;  x = 6 

 

e) 15x^2 +14x -8 = 0 

 

(3x +4)(5x -2)

 

x= -4/3 ; x = 2/5 

 

f) x^2+2 -3x =0 

 

(x-2)(x-1)

 

g) 10x^2 -11x -6 

 

(5x +2)(2x -3) = 0 

 

x= -2/5 ;  x= 3/2